Utilización de cloruro de berberina como indicador fluorescente en cromatografía (1990)
Many substances isolated from natural products can not be detected by means of UV ligth. Berberine Hydrochioride was used as a fluorescent indicator in thin layer chromatography for high molecular weight substances with low insaturation. This new aplication amplifies the use of Berberine already used for satured compounds. Results of standards and substances isolates from natural products, in the Chemistry Department at National University, are presented.